1988
DOI: 10.1007/bf00014276
|View full text |Cite
|
Sign up to set email alerts
|

Dietary variations of predaceous caddisfly larvae (Trichoptera: Rhyacophilidae, Polycentropodidae and Arctopsychidae) from British Columbian streams

Abstract: The diets of larval Rhyacophilidae (Rhyacophila inculta), Polycentropodidae (Polycentropus variegatus) and Arctopsychidae (Parapsyche almota and R elsis) from five streams in the University of British Columbia Research Forest, British Columbia (Canada), are recorded and related to feeding mode/constructional activities and prey representation in the habitat. Particular attention was paid to the extent of dietary overlap and the degree of intraspecific dietary variations between streams.An overall similarity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Decrease of trichopteran predatory pressure in the potamal was also described in many recent studies dealing with the predation effects of trichopteran larvae on the spatial and temporal dynamics of benthic macroinvertebrates (MECOM, 1972;HILLDREW and TOWNSEND, 1980;MARTIN, 1985;DUDGEON and RICHARDSON, 1988;BASAGUREN and ORIVE, 1989;LANCASTER et al, 1990;MUOTKA, 1993;HABDIJA et al 1997). In the potamal we found no predatory trichopterans.…”
Section: Discussionmentioning
confidence: 60%
“…Decrease of trichopteran predatory pressure in the potamal was also described in many recent studies dealing with the predation effects of trichopteran larvae on the spatial and temporal dynamics of benthic macroinvertebrates (MECOM, 1972;HILLDREW and TOWNSEND, 1980;MARTIN, 1985;DUDGEON and RICHARDSON, 1988;BASAGUREN and ORIVE, 1989;LANCASTER et al, 1990;MUOTKA, 1993;HABDIJA et al 1997). In the potamal we found no predatory trichopterans.…”
Section: Discussionmentioning
confidence: 60%
“…In particular, within the filter-feeding group Hydropsychidae, they suggest Parapsyche, Arctopsyche and Diplectrona are typical of headwater streams. Parapsyche and Arctopsyche occupy steep streams, using the microhabitats between cobbles and boulders with hydraulic jumps to place their nets, associated with their predatory habits [42,79]. Diplectrona appears to require cool water [80].…”
Section: Invertebratesmentioning
confidence: 99%
“…Both families build nets and some species are adapted to living in low-velocity streams (Dudgeon and Richardson 1988;Wiggins 1996). Examination of individual families, however, revealed that larval Philopotamidae (a collector-filterer) and larval and adult Polycentropodidae (a predator) were more common in the less persistent streams.…”
Section: Influence Of Stream Persistence Class (Perennial Intermittementioning
confidence: 99%